Purificação e caracterização de ß-galactosidases citosólicas e de parede celular de raízes de plântulas de Vigna unguiculata (L.) Walp. semeadas na presença e na ausência de NaCl - Barbosa, Gislainy Karla da Costa (2007)
The (3-galactosidase are one of hydrolases wich are involved in the modification of cell wall components throughout the cellular elongation process and plant growth. To attempt elucidate the role of these enzymes during this process, display the purification and characterization of citosolic and associated (3-galactosidases from Pitiúba cowpea [Vigna unguiculata (L.) Walp.] roots of seedlings in development stages III and VIII, wich were sown in distilled water (control treatment) and in NaCI (salt treatment) [...]